MODELING OF CONVECTIVE FLOWS IN PNEUMOBASED OBJECTS. Part 1 - B. M. Khrustalyov; V. D. Akelyev; T. V. Manyushinets; M. F. Kostevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A computer modeling process of three-dimensional forced convection proceeding from computation of thermodynamic parameters of pneumo basic buildings (pneumo supported structures) is presented. The mathematical model of numerical computation method of temperature and velocity fields, pressure profile in the object is developed using the package Solid works and is provided by grid methods on specified software. Special Navier–Stokes, Clapeyron–Mendeleev, continuity and thermal-conductivity equations are used to calculate parameters in the building with four supply and exhaust channels. Differential equations are presented by algebraic equation systems, initial-boundary conditions are changed by differential conditions for mesh functions and their solutions are performed by algebraic operations. In this article the following is demonstrated: in pneumo basic buildings convective and heat flows are identical structures near the surfaces in unlimited space, but in single-multiply shells (envelopes)circulation lines take place, geometrical sizes of which depend on thermal-physical characteristics of gas(air)in envelopes, radiation reaction with heated surfaces of envelopes with  sphere, earth surface, neighboring buildings. Natural surveys of pneumo-basic buildings of different purposes were carried out in Minsk, in different cities of Belarus and Russia, including temperature fields of external and internal surfaces of air envelopes, relative humidity, thermal (heat)flows, radiation characteristics and others.The results of research work are illustrated with diagrams of temperature, velocity, density and pressure dependent on coordinates and time.